Bahasa Melayu di Kerajaan Buton (Studi berdasarkan naskah kuno koleksi Abdul Mulku Zahari di Buton) - Niampe, La (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Buton is one of the Malay Kingdoms located in Southeast Sulawesi. As time went by, more and more people from the Malay world came to Buton. This was due to the strategic position of Buton as a trade route in Eastern Nusantara. In addition, this movement was encouraged by the intention to spread Islam. As part of the Malay Kingdoms, the use of the Malay language was indispensable. The script collection of ancient texts of the Buton Kingdom (Abdul Mulku Zahari’s collection) indicates that the Malay language was taken as one of the official languages used in the kingdom, alongside Arabic and Wolio. From the collection, it was found that Malay scripts were older than Arabic and Wolio scripts (according to their colophons). This language was also used to write manuscripts on religious teachings, official letters of the kingdom, adat laws, history, genealogy, literature, traditional medicine, language instruction, and primbon.